Comparison of MR imaging features of solid pseudopapillary neoplasm of pancreas between male and female patients. Issue 11 (November 2015) - Sur, Young Keun; Lee, Jei Hee; Kim, Jai Keun; Park, Min Jung; Kim, Bohyun; Park, Mi-Suk; Choi, Jin-Young; Kim, Young Bae; Lee, Dakeun
Abstract: Purpose: To evaluate MR imaging features of solid pseudopapillary neoplasms (SPN) in male patients and to compare them with the MR imaging features in female patients. Materials and methods: Fifty patients who were histologically confirmed as SPN (M:F = 8:42, mean age = 36.4 years) with preoperative MRI were included. The following imaging features were reviewed: size, location, shape, margin, encapsulation, solid-cystic ratio, pancreatic duct dilatation, parenchymal atrophy, T1 signal intensity, T2 signal intensity, and morphological and dynamic pattern of enhancement. The statistical differences between male and female patients were analyzed. Results: The average age of male patients (50.8 ± 4.1 years) was significantly higher ( p < 0.01) than female patients (33.7 ± 2.0 years). The shape of SPN in male patients was predominantly lobulated ( n = 6/8, 75.0%) compared to female patients, in whom oval shaped SPN was most prevalent ( n = 26/42, 61.91%) ( P = 0.02). SPN in male patients contained less cystic component (solid, n = 4/8, 50.0%; mainly solid, n = 4/8, 50.0%) while cystic ( n = 5/42, 11.90%) or mainly cystic ( n = 13/42, 30.95%) lesions were significantly more prevalent in female patients ( P = 0.03). The majority of SPNs in both groups showed progressive heterogeneous enhancement pattern. Other MR imaging features showed no significant differences between the male and female patients. Conclusion: On MRI, SPN in male patients appeared as mainly solid mass with a lobulating contour and heterogeneous progressive enhancement occurring at an older age than female patients. Recognition of imaging features of SPN in male patients compared to typical SPN in female patients should assist in correct differentiation of SPN from other pancreatic tumors.